Combination of Two‐Stage Continuous Feeding and Optimized Synthetic Medium Increases Lipid Production in Lipomyces starkeyi - Chih‐Chan Wu; Kenji Okano; Pijar Religia; Yuki Soma; Masatomo Takahashi; Yoshihiro Izumi; Takeshi Bamba; Kohsuke Honda (Engineering in Life Sciences)
ABSTRACT The oleaginous yeast Lipomyces starkeyi is recognized for its remarkable lipid accumulation under nitrogen‐limited conditions. However, precise control of microbial lipid production in L. starkeyi remains challenging due to the complexity of nutrient media. We developed a two‐stage fed‐batch fermentation process using a well‐defined synthetic medium in a 5‐L bioreactor. In the first stage, the specific growth rate was maintained at a designated level by maximizing the cell density through optimizing the feeding rate, molar carbon‐to‐nitrogen (C/N) ratio, and phosphate concentration in feeding media, achieving a high cell density of 213 ± 10 × 107 cells mL−1. In the second stage, we optimized the molar C/N ratio in the feeding medium for lipid production and achieved high biomass (130 ± 5 g L−1), lipid titer (88 ± 6 g L−1), and lipid content (67% ± 2% of dry cellular weight). Our approach yielded a high lipid titer, comparable to the highest reported value of 68 g L−1 achieved in a nutrient medium, by optimizing cultivation conditions with a synthetic medium in L. starkeyi. This highlights the importance of well‐established yet powerful bioprocess approaches for the precise control of microbial cultivation.